2021
DOI: 10.1139/cgj-2018-0712
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the coefficient of restitution of grain against block interfaces for natural and engineered materials

Abstract: The coefficient of restitution (COR) is an important input parameter in the numerical simulation of granular flows, as it governs the travel distance, the lateral spreading and the design of barriers. In this study, a new custom-built micro-mechanical impact loading apparatus is presented along with impact experiments on engineered and natural materials. The COR and energy loss of various grains and base block combinations are studied, including fairly regular shaped Leighton Buzzard sand (LBS) grains as a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 71 publications
5
41
0
Order By: Relevance
“…A recent study by Marinack et al [32] showed that the effect of air drag on the grain velocity (for the range of velocities used in this study) is negligible and the COR values only differ by less than 1%. Repeatability of the tests and data acquisition using the impact loading apparatus used in the present study was presented by Sandeep et al [22].…”
Section: Testing Program and Analytical Expressionsmentioning
confidence: 77%
See 4 more Smart Citations
“…A recent study by Marinack et al [32] showed that the effect of air drag on the grain velocity (for the range of velocities used in this study) is negligible and the COR values only differ by less than 1%. Repeatability of the tests and data acquisition using the impact loading apparatus used in the present study was presented by Sandeep et al [22].…”
Section: Testing Program and Analytical Expressionsmentioning
confidence: 77%
“…A micromechanical impact apparatus was used to measure the COR of grain and base block impacts for different material combinations. This apparatus was developed inhouse and is described Materials 2020, 13, 814 3 of 14 in a recent study by Sandeep et al [22], but for completeness, it is detailed here as well. An image of the impact loading apparatus is shown in Figure 1.…”
Section: Micromechanical Impact Apparatusmentioning
confidence: 99%
See 3 more Smart Citations